Book language and its implications for children’s language, literacy, and development - Nation, K; Dawson, NJ; Hsiao, Y (SAGE Publications, 2022)
The onset of literacy marks a significant change in children’s development. Written language is more complex than everyday conversation, and even books targeted at preschoolers contain more varied words and more complex syntax than child-directed speech does. We review the nature and content of children’s book language, focusing on recent large-scale corpus analyses that systematically compared written and spoken language. We argue that exposure to book language provides opportunities for learning words and syntactic constructions that are only rarely encountered in speech and that, in turn, this rich experience drives further developments in language and literacy. Moreover, we speculate that the range, variety, depth, and sophistication of book language provide key input that promotes children’s social and emotional development. Becoming literate changes things, and researchers need to better understand how and why reading experience shapes people’s minds and becomes associated with a range of skills and abilities across the life span.